ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KENDAL TAHUN 2014-2018 - Deni Ariyanti; Resi Yudhaningsih (Politeknik Negeri Semarang, 2020)
This research was conducted to find out how much the effectiveness and contribution of regional taxes on Regional Original Revenue (PAD), as well as to know how the relationship between local taxes and Kendal Regency Regional Revenue (PAD). Data collection methods used are interviews and documentation. The writing method used is description and exposition. The result of the discussion is that the level of local tax effectiveness is very effective with an average of 126.49%, the criteria for regional tax contribution to regional original income are quite good with an average of 30.47%, the results of regression analysis show positive results which means the growth in number Regional Tax revenues will result in the growth of Regional Original Income, and the results of the correlation analysis show that the regional tax on Kendal District Original Revenue (PAD) has a very strong relationship with a coefficient r of 0.89 so that if the local tax increases then the Local Revenue Kendal Regency will alsoincrease.Keywords: Regional Taxes, Regional Original Revenue, Effectiveness, and Contributions.